Pengejawantahan Pendekatan Storytelling dalam Pemahaman Membangun Diagram Alir Data - Herlinda Herlinda; Randi Ramliyana; Erlin Windia Ambarsari (Jurnal Pendidikan Informatika (EDUMATIC), 2021)
Throughout the System Development Life Cycle (SDLC), establishment the software through various phases. System design is one of the most crucial aspects of the SDLC. The Data Flow Diagram (DFD) is a model to build the system. The purpose of the research was to make it easier for people to comprehend the diagram by carefully preparing DFD, then it created software according to the DFD design. Storytelling is the method employed, and it pertains to qualitative ways for creating language patterns. As a design reference, it needs to make the DFD pattern subsequently. The research mimics two scenarios to reflect previous research on the same principle. According to the findings of this study, there are two significant disparities. The first scenario concerns system user activity, whereas the second concerns software performance. Therefore, it corresponds to the core notion of input-process-output; narrative scenario 1 is more consistent and easier to design in the processed results created from sentence patterns to DFD patterns. Scenario 2, on the other hand, connects many process symbols to processes, complicating the DFD design. Finally, scenario 2 is beneficial for requirements elicitation, whereas scenario 1 applies to business procedures.